Coordination Dynamics and Coordination Mechanism of a New Type of Anticoagulant Diethyl Citrate with Ca2+ Ions - Jin Han; Jun-Fa Xue; Meng Xu; Bao-Song Gui; Li Kuang; Jian-Ming Ouyang (Bioinorganic Chemistry and Applications)
Diethyl citrate (Et2Cit) is a new potential anticoagulant. The coordination dynamics and coordination mechanism of Et2Cit with Ca2+ ions and the effect of pH on the complex were examined. The result was compared with that for the conventional anticoagulant sodium citrate (Na3Cit). The reaction order (n) of Et2Cit and Na3Cit with Ca2+ was 2.46 and 2.44, respectively. The reaction rate constant (k) was 120 and 289 L·mol−1·s−1. The reverse reaction rate constant (kre) was 0.52 and 0.15 L·mol−1·s−1, respectively. It is indicated that the coordination ability of Et2Cit with Ca2+ was weaker than that of Na3Cit. However, the dissociation rate of the calcium complex of Et2Cit was faster than that of Na3Cit. Increased pH accelerated the dissociation rate of the complex and improved its anticoagulant effect. The Et2Cit complex with calcium was synthesized and characterized by elemental analysis, XRD, FT-IR, 1H NMR, and ICP. These characteristics indicated that O in –COOH and C–O–C of Et2Cit was coordinated with Ca2+ in a bidentate manner with 1 : 1 coordination proportion; that is, complex CaEt2Cit was formed. Given that CaEt2Cit released Ca2+ more easily than Na3Cit, a calcium solution was not needed in intravenous infusions using Et2Cit as anticoagulant unlike using Na3Cit. Consequently, hypocalcemia and hypercalcemia were avoided.